(untitled) - Bliesner, David M. (Hoboken, N.J., 2006)
In today's litigious environment, pharmaceutical laboratories are subject to ever stricter operational guidelines as mandated by the FDA, and must be able to establish and demonstrate sustainable operational practices that ensure compliance with the current good manufacturing practice (CGMP) regulations. David Bliesner's Establishing a CGMP Laboratory Audit System: A Practical Guide is designed to provide laboratory supervisors and personnel with a step-by-step, hands-on audit system that they can rely on to ensure their facility remains compliant with all current and future requirements. Focusing on a "team approach," the author uses detailed flowcharts, checklists, and descriptions of the auditing process to help readers develop a new audit system or upgrade their current system in order to: Improve current compliance; Demonstrate sustainable compliance; Produce data for federal inspections; Avoid regulatory action
Keywords: Pharmaceutical industry,Drugs,Drug Industry,Ngành công nghiệp dược phẩm; Law and legislation,standards; United States,United State,United States,Hoa Kỳ